2018
DOI: 10.1038/s41598-018-27725-2
|View full text |Cite
|
Sign up to set email alerts
|

Phenology drives species interactions and modularity in a plant - flower visitor network

Abstract: Phenology is often identified as one of the main structural driving forces of plant – flower visitor networks. Nevertheless, we do not yet have a full understanding of the effects of phenology in basic network build up mechanisms such as ecological modularity. In this study, we aimed to identify the effect of within-season temporal variation of plant and flower visitor activity on the network structural conformation. Thus, we analysed the temporal dynamics of a plant – flower visitor network in two Mediterrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 44 publications
2
53
0
Order By: Relevance
“…With lower modularity and more generalist species, we expect a stronger relationship between phenology and the intensity of interactions because interactions are less influenced by insect preferences and more by seasonal rhythm and flower availability (Dormann et al ). Thus, different phenophases might correspond to different compartments (Martín González et al , Morente‐López et al ), as observed in CG, FAL, LAR and R where higher overlap corresponded to higher numbers of observed visits. Although phenology improved model fit (Table 2), its effect size was modest (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…With lower modularity and more generalist species, we expect a stronger relationship between phenology and the intensity of interactions because interactions are less influenced by insect preferences and more by seasonal rhythm and flower availability (Dormann et al ). Thus, different phenophases might correspond to different compartments (Martín González et al , Morente‐López et al ), as observed in CG, FAL, LAR and R where higher overlap corresponded to higher numbers of observed visits. Although phenology improved model fit (Table 2), its effect size was modest (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…plant and pollinators). Year of sampling was included as a predictor variable in models, as network metrics can vary across years and seasons (Morente-López, Lara-Romero,Ornosa, & Iriondo, 2018;Olesen, Stefanescu, & Traveset, 2011). We repeated these LMMs including only pollinator species common to all elevations.…”
mentioning
confidence: 99%
“…The use of trait-based and phylogenetic tree-based proxies lies in the idea of niche complementarity, whereby species with similar functional traits and thus partially overlapping niches are expected to perform similar and, to a certain degree, redundant, ecological roles (Pigot et al 2016). Frugivores with distinct traits tend to be more functionally specialized, interacting with plants that are less frequently visited by other members of the community, thus increasing specialization (Junker et al 2012, Maglianesi et al 2015, Watts et al 2016, Tinoco et al 2017) and modularity (Maruyama et al 2014, Morente-López et al 2018) of networks. On the other hand, it was not detected an effect of species' traits on metrics of host-parasitoid networks (Morris et al 2014).…”
Section: Introductionmentioning
confidence: 99%